2022
DOI: 10.3390/biom12020218
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differentiation of Human Dental Mesenchymal Stem Cells Induced by ATRA and UDP-4: A Comparative Study

Abstract: Human mesenchymal stem cells (MSC) are multipotent stem cells, which are isolated from various sources. Currently, there is a worldwide interest for dental MSC to be used against neurodegenerative diseases, since they derive from the neural crest and express embryonic stem cell markers. This fact prompted us to explore their potential for neural trans-differentiation in culture. We employed all-trans-retinoic acid (ATRA) and 2-(3-ethylureido)-6-methylpyridine (UDP-4) to induce neural differentiation of human M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The ATRA is commonly used to induce neurogenic differentiation of multiple cell lines and stem cells such as SH-SY5Y human neuroblastoma cells [107,108], P19 mouse embryonal carcinoma cell line [109,110], embryonic stem cells [111,112], and mesenchymal stem cells [113]. However, Takahashi et al [114] and Goldie et al, [74] reported that ATRA alone results in immature neural differentiation of SH-SY5Y and neural stem cells and should be supplemented in combination with neurotrophin such as BDNF to establish full neural maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The ATRA is commonly used to induce neurogenic differentiation of multiple cell lines and stem cells such as SH-SY5Y human neuroblastoma cells [107,108], P19 mouse embryonal carcinoma cell line [109,110], embryonic stem cells [111,112], and mesenchymal stem cells [113]. However, Takahashi et al [114] and Goldie et al, [74] reported that ATRA alone results in immature neural differentiation of SH-SY5Y and neural stem cells and should be supplemented in combination with neurotrophin such as BDNF to establish full neural maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Howeve differences have been observed in other characteristics, such as the immunophenotyp where the expression of some markers may vary. In addition, although they have simil multipotentialities for differentiation toward chondrocytes and osteoblasts, the adipogenic capacity is lower than that of other tissues, such as BM [58,60,61,62,63,64 Moreover, D-MSCs derived from neural crest cells possess an increased potential f differentiation into neural cells [65,66,67,68]. Taken together, these findings indicate th The most common methods used to obtain MSCs are explant and enzymatic digestion.…”
Section: Mscs From Dental and Periodontal Tissuesmentioning
confidence: 97%
“…In addition, although they have similar multipotentialities for differentiation toward chondrocytes and osteoblasts, their adipogenic capacity is lower than that of other tissues, such as BM [58,[60][61][62][63][64]. Moreover, D-MSCs derived from neural crest cells possess an increased potential for differentiation into neural cells [65][66][67][68]. Taken together, these findings indicate that although all of these sources originate in related anatomical regions, the biological properties of each can vary, and of particular importance is their immunosuppressive capacity due to their relevance in clinical protocols.…”
Section: Mscs From Dental and Periodontal Tissuesmentioning
confidence: 99%
“…Derived from the neural crest, dental MSCs uniquely express neural markers, secrete neurotrophic factors, and combine MSC-like characteristics with immunomodulation and neural features [ 73 ]. With their neural crest lineage, neuronal markers, and expression of neurotrophic factors, along with the potential for neurogenic differentiation, these cells are actively researched for their applications in treating neuronal diseases and injuries [ 74 , 75 ]. Recent studies highlight their promising role in neural tissue engineering for nerve regeneration, particularly in the treatment of SCI.…”
Section: The Neurodegenerative Potential Of Dental Stem Cellsmentioning
confidence: 99%